PERUBAHAN CITRA KAWASAN KOTA BARU YOGYAKARTA - Suwanto, Noor (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2018)
Abstract:. New Town area built using the concept of Garden City is currently experiencing many changes so that the image of the Kota Baru area is difficult to recognize in accordance with the concept of Garden City. Changes experienced by Kota Baru area is changing land use, visual changes in buildings, open spaces change. This study aims to determine the image of the Kota Baru area in accordance with the concept of Garden City in the early days of established, the present, changes in the image of the region, and efforts to strengthen the image of the region. The research method used qualitative method which then analyzed descriptively. The study was conducted on the entire Kota Baru area based on Garden City's theory by Ebenezer Howard and Thomas Karsten, in the use of Kevin Lynch City image imagery with aspects of Identity, Structure, and Meaning. The result of this research is that the image of the area at the beginning was very strongly visible from all aspects of area image. But the image of surveillance at the time of now a days not all aspects look strong, the strongest aspect seen in the path element, and the sense of the enclosure (enclosure).Keyword: Garden City, image of Kota Baru, change of imageÂ Abstrak: Kawasan Kota Baru yang dibangun menggunakan konsep Garden City saat ini kondisinya sudah mengalami banyak perubahan sehingga citra dari kawasan Kota Baru sulit untuk dikenali sesuai dengan konsep Garden City. Perubahan yang dialami kawasan Kota Baru adalah tata guna lahan berubah, perubahan visual bangunan, ruang-ruang terbuka mengalami perubahan. Penelitian ini bertujuan untuk mengetahui citra kawasan Kota Baru sesuai dengan konsep Garden City pada masa awal didirikan, masa sekarang, perubahan citra kawasan, dan upaya untuk menguatkan citra kawasan. Metode penelitian menggunakan metode kualitatif yang kemudian dianalisis secara deskriptif. Penelitian dilakukan pada seluruh kawasan Kota Baru berdasarkan teori Garden City oleh Ebenezer Howard dan Thomas Karsten, di gunakan teori citra Kota Kevin Lynch dengan aspek Identitas, Struktur, dan Makna. Hasil penelitian yang didapatkan adalah citra kawasan pada awal didirikan sangat kuat terlihat dari semua aspek citra kawaan. Tetapi citra kawasan pada masa sekrang tidak semua aspek terlihat kuat, aspek paling kuat terlihat pada elemen path, dan rasa akan keterlingkupan (enclosure).Kata Kunci: konsep Garden City, citra Kota Baru, perubahan citra